Continuous glucose monitoring and advanced glycation endproducts for prediction of clinical outcomes and development of cystic fibrosis-related diabetes in adults with CF - Scully, Kevin J.; Brenner, Laura; Martin, Kimberly; Ruazol, Melanie; Sawicki, Gregory S.; Uluer, Ahmet; Neuringer, Isabel; Yonker, Lael M.; Sicilian, Leonard; Putman, Melissa S. (Frontiers in Endocrinology, 2024)
Introduction: We previously reported that CGM measures of dysglycemia are superior to hemoglobin A1c (HbA1c) in distinguishing those with and without CFRD. However, little is known about the long-term predictive value of CGM for both the development of CFRD and their effect on key clinical outcomes. There have been no studies investigating advanced glycation endproducts (AGE) in people with CF. Methods: In this prospective observational study, CGM and HbA1c were measured at 2 to 3 time points 3 months apart in 77 adults with CF. Participants without CFRD at enrollment underwent OGTT, and all participants had AGE readings. Follow up data were collected by review of medical records at 1- and 2-years. We applied multivariable linear regression correlating glycemic measures to change in key clinical outcomes (weight, BMI, FEV1), and logistic regression comparing baseline glycemic data to CFRD development during those 2-year. Results: Twenty-five participants had pre-existing CFRD at enrollment, and six were diagnosed with CFRD by baseline OGTT. When adjusting for age, gender, and ETI use, multiple CGM measures correlated with weight and BMI decline after one year but not two years. Baseline HbA1c and CGM did not predict FEV1 decline (p>0.05). In the 46 participants without CFRD at baseline, two were diagnosed over the following two years, but baseline CGM measures did not predict CFRD progression. Baseline AGE values were higher in individuals with CFRD and correlated with weight and multiple glycemic measures (HbA1c, AG, SD, CV, TIR, % time >140, >180, >250). AGE values correlated with FEV1 decline at year-1 and weight decline at year-1 and year-2. Discussion: Several CGM measures of dysglycemia were predictive of future decline in weight and BMI over one year in adults with CF with and without CFRD. No baseline glycemic variables predicted progression to CFRD over 2 years. This is the first report correlating AGE levels with key clinical and glycemic measures in CF. Limitations include the small number of participants who developed CFRD (n=2) during follow up and the initiation of ETI. These results provide additional data supporting the potential role for CGM in identifying clinically significant dysglycemia in CF.